Control of Four Switch Three Phase Inverter Fed Induction Motor Drives Based Speed and Stator Resistance Estimation - Mohamed K Metwally (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
This paper presents sensorless position and speed control for a four-switch three-phase inverter (FSTPI) fed induction motor drive. Accurate knowledge of stator resistance is of utmost importance for correct operation of a number of speed sensorless induction motor control schemes in the low speed region. Since stator resistance inevitably varies with operating conditions, stable and accurate operation at near-zero speed requires an appropriate identification algorithm for the stator resistance. The paper proposes such an identification algorithm, which is developed for the rotor flux based model reference adaptive system (MRAS) type of the speed estimator in conjunction with a rotor flux oriented control scheme. In this speed estimation method only one (out of the two available) degree of freedom is utilized for speed estimation. It is utilize the second available degree of freedom as a mean for adapting the stator resistance. The parallel stator resistance and rotor speed identification algorithm is developed in a systematic manner, using Popov’s hyper stability theory. It increases the complexity of the overall control system insignificantly and enables correct speed estimation and stable drive operation at near-zero speeds. The proposed speed and position estimator with parallel stator resistance identification for FSTPI fed induction motor at very low speed under high load operation is verified by simulation and experimental results. The results show the robustness of the proposed method with FSTPI.DOI: http://dx.doi.org/10.11591/ijpeds.v4i2.5057